A Study of the Implementation of Internalized Interactive Multimedia Learning Models in Life Skills Education of Student at Primary School of it Al-Fitrah Binjai - Epi Supriyani Siregar (BIRCU, 2020)
Education is a form of human culture which is a prerequisite for development. Therefore, it is necessary to implement life skills education in learning with the intention of integrating life skills through the implementation of interactive multimedia-based learning models. This study aims to determine the effectiveness of interactive multimedia-based learning models internalized in life skills education that can improve learning outcomes of students in thematic lessons. This research uses a qualitative research approach. Data are analyzed using descriptive analysis techniques to determine the effectiveness of interactive multimedia based learning models in life skills education. The results show that the implementation of an interactive multimedia-based learning model with internalized life skills education involve the realm of personal skills, namely smiling, greeting, and being polite every day in the school environment at primary school of IT Al-Fitrah Binjai. On the other hand, the realm of academic skills involve the variants of learning methods by developing skills that are adjusted to the basic competency standards on the subject of teaching and learning activities. Internalized interactive multimedia-based learning models in life skills education can improve cognitive abilities, affective, and psychomotor students. By internalizing life skills education can improve student learning outcomes, so it is very effective to use.